Perlindungan Hukum bagi Buruh Migran Terhadap Tindakan Perdagangan Perempuan - Devi Rahayu (Jurnal Hukum IUS QUIA IUSTUM, 2011)
The problem which was appointed in this research; first, is there any trafficking of women in cases happened in the process of migrant workers delivery in Kabupaten Bangkalan and Sampang? Second, can the valid regulations be used to conduct the protection for migrant workers in the process of migrant workers delivery from the trafficking of women as well as the appropriate legal protection in order to prevent the trafficking of women practice? The method used in this research was juridical empiric, while the data collecting method was; observation, structured interview, and deep interview. The data analyzing method was performed by content analysis, with the use of formal interpretation method, analogy, and extensive. The result showed that in the process of the migrant workers delivery, there were elements of human trafficking, such as; over-limited actions, violence or threats of violence, fraud, debt bondage, violence with abuse of power, and forced labor or the condition similar with slavery. The regulation of migrant workers delivery has not entirely arranged the related protection on trafficking action.Key words : Legal protection, migrant workers, trafficking of women